A Photo‐Stable Indocyanine Green and Rapamycin Co‐Delivery System Based on Poly(Glutamic Acid)‐Modified Manganese Phosphate for Synergetic Tumor Therapy. Issue 12 (15th October 2019) - Hao, Yongwei; Zheng, Cuixia; Qiang, Hong; Chen, Hongli; Wang, Fan; Zhang, Jinjie; Zhang, Hongling; Wang, Lei; Zhang, Zhenzhong; Zhang, Yun
Abstract: Some manganese‐based nanomaterials quench the fluorescence of photosensitizers, which strongly quenches fluorescence emission and suppresses reactive oxygen species (ROS) production due to the photo‐induced charge transfer from the excited photosensitizer to nanomaterials. In this study, to overcome these disadvantages, amorphous porous manganese phosphate (MnP) nanoparticles are used for loading indocyanine green (ICG), and a broader ICG absorbance width instead of weakened fluorescence profile is observed, resulting in higher stability and phototherapy efficiency under 808 nm irradiation. Moreover, autophagy inhibition obviously weakens the ICG‐mediated phototherapy to breast cancer cells. On this foundation, an autophagy promoter rapamycin (RAPA) and ICG are co‐loaded into the MnP nanoparticles, and further decorated with biocompatible poly(glutamic acid). As expected, this stable nanoplatform released 80.0±4.1% agents at low pH compared to that 32.0±4.8% at normal pH, indicating a clear pH‐responsive release profile. Uniting phototherapy with autophagy promoter by this system is found to achieve synergistic outcomes as evidenced by the smaller relative tumor volume of 1.8±0.4. Overall, this work provides the first photo‐stable manganese‐based nanomaterial without fluorescence quenching profile for achieving multiple desirable therapeutic performances. Abstract : In the spotlight : This work provides the first photo‐stable manganese‐based nanomaterial without fluorescence quenching for achieving multiple desirable therapeutic performances. The amorphous porous manganese phosphate (MnP) nanoparticles are found to be excellent vehicles for delivering indocyanine green (ICG) because a broader ICG absorbance width instead of a weakened fluorescence profile is observed, resulting in higher stability and phototherapy efficiency under 808 nm irradiation.